2018
DOI: 10.1111/ijpo.12481
|View full text |Cite
|
Sign up to set email alerts
|

A pilot randomized controlled trial examining the impact of a sleep intervention targeting home routines on young children's (3–6 years) physical activity

Abstract: Summary Background Given evidence suggesting that sleep impacts on metabolic processes, interventions targeting sleep may improve child physical activity (PA). Objectives To describe the potential effect of an intervention to increase sleep on young children's (3–6 years) moderate to vigorous PA (MVPA) and total PA. To determine adherence to the intervention, impact on sleep duration as well as feasibility, uptake and acceptability was also assessed. Methods Pilot randomized controlled trial with 76 parent–chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 33 publications
1
34
0
Order By: Relevance
“…Evidence in adults suggests that total sleep deprivation could lead to lower resting and postprandial energy expenditure, while chronic partial sleep deprivation could cause the feeling of fatigue, which in turn may reduce physical activity and increase sedentary behaviour . It has been reported in children that short sleep duration is associated with decreased physical activity and increased screen time …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence in adults suggests that total sleep deprivation could lead to lower resting and postprandial energy expenditure, while chronic partial sleep deprivation could cause the feeling of fatigue, which in turn may reduce physical activity and increase sedentary behaviour . It has been reported in children that short sleep duration is associated with decreased physical activity and increased screen time …”
Section: Discussionmentioning
confidence: 99%
“…32 Evidence in adults suggests that total sleep deprivation could lead to lower resting and postprandial energy expenditure, 33 while chronic partial sleep deprivation could cause the feeling of fatigue, 34 which in turn may reduce physical activity and increase sedentary behaviour. 35 It has been reported in children that short sleep duration is associated with decreased physical activity 27,36 and increased screen time. 37 Although longitudinal studies in preschool-aged children have predominantly suggested that total sleep duration is negatively associated with weight gain overtime or later adiposity, 11,17,25 in our study, there was no prospective association between total sleep duration and adiposity after 12 months.…”
Section: Overall Discussionmentioning
confidence: 99%
“…All of included studies were published in 2012 or later, among which 7 were published in 2015 or later. Of them, 4 studies from Australia [38,40,45,46], 3 from the United States [31,42,44]. The United Kingdom [47], Germany [43], Finland [41], Norway and Sweden [39] each have one study.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…A total of 1596 articles were searched from each database, 1585 articles were excluded according to the inclusion and exclusion criteria. Finally, 11 articles were included in this study [31,[38][39][40][41][42][43][44][45][46][47]. (Fig.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation